Regulatory B Cells Are Functionally Impaired in Patients Having Hemophilia A With Inhibitors. (May 2018) - Boulassel, Mohamed-Rachid; Al-Ghonimi, Maryam; Al-Balushi, Badriya; Al-Naamani, Amal; Al-Qarni, Zahra; Wali, Yasser; Elshinawy, Mohamed; Al-Shezawi, Maryam; Khan, Hamad; Nazir, Hanan; Khater, Doaa; Pathare, Anil; et al.
Development of inhibitors remains a major clinical complication in patients with hemophilia A receiving replacement therapy with factor VIII (FVIII). Understanding the immune mechanisms involved in the development of inhibitors can provide valuable information about pathways to human tolerance. Recent evidence indicates that B regulatory (Breg) cells play a pivotal role in controlling the production of antibodies (Abs) while promoting follicular T helper (Tfh) cells and monocytes, expressing the low-density lipoprotein receptor-related protein (LRP/CD91), which is involved in FVIII intake from the circulation. We studied circulating levels of Breg cells along with Tfh cells and the expression of LRP/CD91 on monocytes in patients with hemophilia A using 8-color flow cytometry and cell culture. Compared to healthy controls, patients with hemophilia A with inhibitors showed a severe reduction in levels of Breg cells and produced less interleukin-10 when activated via the CD40 signaling pathway. In addition, patients with hemophilia A with inhibitors exhibited an overexpression of LPR/CD91 on monocytes and normal levels of Tfh cells. Levels of Breg cells were not significantly related to LPR/CD91 although negative associations were evidenced. Collectively, these results provide new insights into the role of Breg cells and LPR/CD91 in the development of inhibitors in patients with hemophilia A.